The Effects of A Peer Support Group Program on Psychosocial Rehabilitation Abilites In Caregivers Of Schizophrenic Patients - เหลียงพานิช พิชญา; สมประเสริฐ ชมชื่น; อิ้มคำ เอกอุมา (Journal of The Royal Thai Army Nurses, 2018)
The purpose of this quasi experimental research, which was divided two pre-posttest groups,was to examine the effects of a peer support group program on psychosocial rehabilitation abilities in caregivers of schizophrenic patients.A research sample of 60 primary caregivers of schizophrenic patients live in Bangkurad district at Nonthaburi that met the inclusion criteria and these were randomly assigned to the experimental and control group, with 30 subjects in each group. The experimental group participated in the peer support group program while the control group received routine caring activities. The research instruments were the following: 1) a personal data questionnaire; 2) the peer support group program; and 3) an ability psychosocial rehabilitation skills scale. The peer support group program was validated for content validity by 3 professional experts and the mental health self-care scale, with a Cronbach alpha coefficient reliability of .92. Data were analyzed by descriptive statistics, dependent t-test, and independent t-test. The findings were as follows:1) the mean score of psychosocial rehabilitation abilities of the schizophrenic patients caregivers after participating in the peer support group program (M = 84.47, SD = 11.01) was statistically significant higher than before participating in the program (M = 35.13, SD = 10.275) (p<.001). 2) The mean difference between pre-post psychosocial rehabilitation abilities scores for the schizophrenic patients’ primary caregivers that participated in the peer support group program ( = 49.34, SD = 11.013) was significantly greater than that for the primary caregivers that received regular caring activities ( = 7.1, SD = 7.352) (p<.001).